First record of a brackish radiolarian (Polycystina): Lophophaena rioplatensis n. sp. in the Río de la Plata estuary - Boltovskoy, D. (2003)
Vertically stratified bottle plankton samples collected in the Río de La Plata estuary (Atlantic coast of South America at ∼35° S) and in coastal waters off Mar del Plata (∼38° S) in December 1999 and November 2001 yielded up to 394 live cells l-1 of a single new nassellarian species: Lophophaena rioplatensis n. sp. (family Plagoniidae). In estuarine waters, the species was recorded at salinities as low as 15.4 p.s.u.; densities in excess of 100 cells l-1 were found at salinities ranging from 16. 9 p.s.u. These extremely high concentrations (the highest ever reported in the literature), as well as the fact that >90% of the individuals recorded contain cytoplasm, indicate that these are self-sustaining populations which thrive in the estuary (and in nearshore coastal waters), probably due to plentiful dissolved silica and an abundant food supply. Lophophaena rioplatensis is the first polycystine brackish-water species described. This finding shows that radiolarian fossils are not unequivocally associated with open-ocean conditions, but may also be useful indicators of coastal and brackish estuarine paleoenvironments.